2012
DOI: 10.1155/2012/867540
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preoperative Weight Loss before Gastric Bypass: A Systematic Review

Abstract: Background. Many insurance companies require obese patients to lose weight prior to gastric bypass. From a previous study by the same authors, preoperative weight at surgery is strongly predictive of weight loss up to one year after surgery. This review aims to determine whether preoperative weight loss is also correlated with weight loss up to one year after surgery. Methods. Of the 186 results screened using PubMed, 12 studies were identified. A meta-analysis was performed to further classify studies (A clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…In bariatric surgery patients, presurgery short period weight loss programs have been reported to be effective in achieving weight loss using LD based on formulated shakes [9]. A recent systematic review by Kadeli et al [23] confirmed the benefit of preoperative weight loss in bariatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…In bariatric surgery patients, presurgery short period weight loss programs have been reported to be effective in achieving weight loss using LD based on formulated shakes [9]. A recent systematic review by Kadeli et al [23] confirmed the benefit of preoperative weight loss in bariatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…%EBMIL and %EWL are not usually used when reporting nonsurgical weight loss trials, which prefer absolute weight or %TWL [15][16][17][18]. For all patients, the use of absolute weight loss is biased against lower-weight individuals because they do not have as much weight to lose [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…For multiple measurements in this period, the closest time before surgery was chosen. This was done to minimize the effect of preoperative weight change and to ensure an accurate preoperative weight [13]. Additional inclusion criteria for analysis are as follows: gender designation, a height between 60 and 240 cm, and an age between 10 and 100 years.…”
Section: Methodsmentioning
confidence: 99%
“…After performing a systematic review of preoperative weight loss before gastric bypass and weight loss outcomes up to 1 year postoperatively, Kadeli and colleagues used the findings from studies with 1-year weight loss data to create a model to depict the weight loss trajectory of 6 hypothetical patients [17]. The authors found, regardless of the amount of weight gained or lost prior to surgery, patients lost a consistent 38 % body weight postoperatively; however, preoperative weight loss increased the total percentage of weight lost overall.…”
Section: Preoperative Mwm and Postoperative Weight Lossmentioning
confidence: 99%